The value of the remuneration of high civil servants in Britain in the 20th century and its implications - Rimington, John D. (2008)
The article traces a large real and comparative decline in the rewards of high civil servants in Great Britain over the 20th century, accelerating since about 1970. It relates this to developments in the market for `high quality' graduates and to changes in public and governmental attitudes which have affected the size, organization and role of the civil service. It discusses possible causes of the decline in top rewards in terms of three explanatory approaches suggested by social scientists - the `institutional', the `cultural', and the views of the `Chicago School'. Finally, following an examination of changes in the way senior British civil servants are now recruited and remunerated, it considers possible outcomes in terms of effects on the part they can play in the governmental process. - Reproduced.
Keywords: Civil service - Great Britain; Civil service